PENGARUH KEBIJAKAN PERMENDAG NO 19 TAHUN 2021 TERKAIT EKSPOR KOPI INDONESIA - Sitompul, Meline Gerarita; Yunarti, Y; Afdal, Muh (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Provisions regarding coffee exports have been regulated several times by Regulation of the Minister of Trade of the Republic of Indonesia until the most recent is Permendag No. 19 of 2021. Since the enactment of this regulation, all coffee business actors have had the opportunity to become Indonesian coffee exporters. This study discusses whether there has been a change in the value of coffee exports before and after Permendag No.19 of 2021 on coffee exports in Indonesia. The research methodology used is quantitative descriptive, using secondary data, which is analyzed using the Paired sample T-test to determine the difference in the average coffee export value before and after Permendag No.19 of 2021. The results show that the Government of Trade No.19 of 2021 influences Indonesian coffee exports. The value of Indonesian coffee exports after the implementation of Permendag No. 19 of 2019 has increased, which is relatively high, as seen from the correlation value, which reaches 96%. The ease of exporting coffee products after the Minister of Trade Regulation is one of the reasons. Permendag No.19 of 2021 in article 50 point (r) makes the coffee export process more accessible so that in addition to reaching a broader market, it also increases the emergence of new exporters. It allows coffee from upstream or farmers to directly access the international market.